PENGEMBANGAN SISTEM INFORMASI PELAYANAN PROSES PENGAJUAN PADA PT. TASPEN BERBASIS WEBSITE MENERAPKAN METODE WATERFALL - Reza Maulana; Yoki Firmansyah; Vellia Widyastuti (Jurnal Informatika Kaputama (JIK), 2021)
PT. Taspen is an agency engaged in civil servant insurance and old age benefits (THT) which is tasked with assisting employees in managing pensioners. At this time, the submission of files for LPH submissions is still not in a systemized manner but is still through the post office or other which causes files to be lost, it is difficult to find files and LKO of PT. Taspen is hampered. The expected goal with this web-based information system will make it easier for local governments to send LPH application files to PT. Taspen and will speed up the work process of PT. Taspen so that the LKO at PT. Taspen is not hampered and will run smoothly, minimizing files that are vulnerable to loss and PT. Taspen is not difficult to find files.